Optimized Design Principles for Silicon‐Coated Nanostructured Electrode Materials and their Application in High‐Capacity Lithium‐Ion Batteries. Issue 12 (3rd August 2017) - Auer, Andrea; Jonasson, Niko Sebastian Willem; Apaydin, Dogukan Hazar; Mardare, Andrei Ionut; Neri, Giulia; Lichtinger, Josef; Gernhäuser, Roman; Kunze‐Liebhäuser, Julia; Portenkirchner, Engelbert
Abstract: Silicon is considered as one of the most promising electrode materials for next‐generation, high‐energy‐density Li‐ion batteries as it demonstrates an exceptionally high specific capacity an order of magnitude beyond that of conventional graphite. The poor capacity retention, caused by the mechanical fracturing of Si because of the extreme volumetric and structural changes upon Li insertion/extraction, has triggered significant attention in the development of Si‐coated nanostructures that can accommodate the lithiation‐induced strain. In parallel, various spectroscopic studies and simulations have been conducted to understand the details of volumetric expansion, fracture, mechanical stress evolution, and structural changes in Si‐coated nanostructures. This publication reports a systematic lithiation/delithiation study of Si‐coated, anodically grown, self‐organized TiO2 nanotubes with different Si‐layer thicknesses. It is demonstrated for the first time that a "sweet spot" for the Si‐coating thickness is formed at which the specific lithiation capacity of the composite material reaches its maximum, which declines quickly for higher coating thicknesses. Furthermore, our results suggest that such a Si‐thickness‐dependent optimum in the specific lithiation capacity is immanent to any Si‐coated nanostructured electrode. Abstract : Optimized design : Si is considered one of the most promising electrode materials for next‐generation, high‐energy‐density lithium‐ion batteries. In this publication, a persuasive correlation is made between the Si‐coating thickness, morphological characteristics, and electrochemical lithium storage performance in anodically grown, self‐organized TiO2 nanotubes with different Si‐layer thicknesses.